A CLINICAL AUDIT OF DIABETES CARE AMONG OLDER ADULTS ADMITTED TO MEDICAL WARDS: A SINGLE CENTRE EXPERIENCE - Min, Lim Tsu; Wei, Terence Ong Ing; Ling, Lim Lee (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Diabetes mellitus is a global health concern, the proportion of people living with diabetes mellitus increases every year, particularly in older adults. The adherence to inpatient glycaemic care guidelines is low. This study aims to assess compliance with inpatient glycaemic care guidelines in medical wards in a single centre and identify areas for improvement. Secondary objectives include assessing the association of achievement of glycaemic targets with 30-day readmission and inpatient mortality rates. METHODOLOGY A retrospective audit of the medical records was conducted for 348 patients living with diabetes admitted to wards 13U and 11U between 1st of April 2023 to 30th July 2023. Point of care standard was set based on Malaysia Endocrine and Metabolic Society inpatient glycaemic management guidelines. The definition of achievement of inpatient glycaemic target is when ≥80% of blood glucose reading lies between 7.0 mmol/L and 10.0 mmol/L during the hospital stay. Statistical analyses were performed using SPSS version 28.0. RESULT Of the 348 patients, 142 (40.8%) of patients were Chinese, 101 (29%) Indians, 97 (27.9%) Malays with a mean age of 77. Overweight was seen in 151 (43.3%) of patients. Adherence to guidelines while using intravenous insulin was poor, highest at 40.6%. Inpatient glycemic targets were achieved in 39% of patients admitted. Patients who did not achieve glycaemic goal targets had a higher rate of 30-day readmissions (67.3% versus 32.7%) and inpatient mortality (69.2% vs 30.8%), although statistically insignificant. CONCLUSION This study highlights low rates of compliance towards glycaemic care guidelines in medical wards 13U and 11U. There was inadequate monitoring, and more than half were found to be non-adherent to guidelines while patients were on continuous insulin infusion. This underscores the need for staff training and improved screening for diabetes complications. Future audits should focus on addressing these deficiencies to enhance patient outcomes.